Investing in the data value chain for nutrition in West Africa - Verstraeten, Roosmarijn (Emergency Nutrition Network, 2021)
Data and the building of country-level data-related capacity is central to achieving the Sustainable Development Goals by 2030. In 2014, the Global Nutrition Report called for a “Nutrition Data Revolution” (IFPRI, 2014). Various actions, investments and initiatives were subsequently shaped that focus on advancing nutrition data at country, regional and global level (Kim, 2016). These include consensus building on sets of standard indicators (e.g., Global Monitoring Framework on Maternal, Infant and Young Child Nutrition) and the inclusion of new indicators in demographic and health surveys, the use of innovative analytic modelling tools to prioritise investments in nutrition (e.g., Nutrition Modelling Consortium) and the synthesis and translation of nutrition data and evidence to inform decision-making for policies, programmes and advocacy (e.g., Transform Nutrition West Africa, Data for Decisions to Expand Nutrition Transformation and National Information Platforms for Nutrition). The Nutrition Data Value Chain (Development Initiatives, 2017) introduced a blueprint for a common language and action around data and information systems to ensure that better data and information is used in decisions (Figure 1). It highlights the need for significant investment in capacity throughout the entire data value chain as well as strong leadership and coordination to promote the use of data to inform decision-making at all levels and across nutrition-relevant sectors.